2008
DOI: 10.1210/me.2007-0383
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol Is an Endogenous Selective Estrogen Receptor Modulator

Abstract: Selective estrogen receptor (ER) modulators (SERMs) are ER ligands whose relative agonist/antagonist activities vary in a cell- and promoter-dependent manner. The molecular basis underlying this selectivity can be attributed to the ability of these ligands to induce distinct alterations in ER structure leading to differential recruitment of coactivators and corepressors. Whether SERM activity is restricted to synthetic ligands or whether molecules exist in vivo that function in an analogous manner remains unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
278
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(299 citation statements)
references
References 63 publications
12
278
1
Order By: Relevance
“…The binding of many xenobiotics and natural products to the ER is consistent with recent evidence that the vertebrate ER has conformational flexibility, which allows it to bind diverse ligands, including 27-hydroxycholesterol [58][59] [ Figure 5], trifluoromethyl-phenylvinyl-E2 [60], as well as tamoxifen and diethylstilbestrol. Thus, there may have been several classes of ligands, including sterols, xenobiotics and natural chemicals that were the original ligand(s) for the ancestral ER.…”
Section: Origin Of Key Steroidogenic Enzymes In Amphioxussupporting
confidence: 80%
“…The binding of many xenobiotics and natural products to the ER is consistent with recent evidence that the vertebrate ER has conformational flexibility, which allows it to bind diverse ligands, including 27-hydroxycholesterol [58][59] [ Figure 5], trifluoromethyl-phenylvinyl-E2 [60], as well as tamoxifen and diethylstilbestrol. Thus, there may have been several classes of ligands, including sterols, xenobiotics and natural chemicals that were the original ligand(s) for the ancestral ER.…”
Section: Origin Of Key Steroidogenic Enzymes In Amphioxussupporting
confidence: 80%
“…Recently, Umetani et al [40] reported that several hydroxylated cholesterols including 27-hydroxycholesterol [27-OH-C], 22R-OH-C, 24S-OH-C and 25-OH-C bound human ER and human ER . 27-OH-C was the most potent, and in some mammalian cells 27-OH-C functions as a partial agonist for human ER and ER [40][41][42][43]. The Kd of 27-OH-C for ER and ER is about 1.3 M and 0.4 M, respectively [40][41][42], which is over 10 3 times higher than the Kd of E2 for human ER and ER [30,40].…”
Section: Was the Ancestral Estrogen A Cholesterol Analog?mentioning
confidence: 91%
“…27-OH-C was the most potent, and in some mammalian cells 27-OH-C functions as a partial agonist for human ER and ER [40][41][42][43]. The Kd of 27-OH-C for ER and ER is about 1.3 M and 0.4 M, respectively [40][41][42], which is over 10 3 times higher than the Kd of E2 for human ER and ER [30,40]. Nevertheless, a Kd of 1 M is physiologically relevant because the circulating concentration of 27-OH-C is from 0.15 to 0.73 M, [40][41][42].…”
Section: Was the Ancestral Estrogen A Cholesterol Analog?mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum and the fluids bathing cells, organs and tissues contain compounds with the potential to imitate estrogens. in this regard, it has been reported that 27-hydroxycholesterol (27Ohc), an oxysterol produced by the intramitochondrial oxidation of cholesterol, may act as a non-conventional SmEr in estradiol-target cells (10,11). in normal subjects, plasma 27Ohc concentration is in the same order of magnitude as the dissociation constant of the complex between Er and 27Ohc, thus assuring their stable association.…”
Section: Introductionmentioning
confidence: 99%